Highly efficient removal of p-arsanilic acid with Fe(II)/peroxydisulfate under near-neutral conditions. (15th June 2020) - Wang, Panxin; He, Xu; Zhang, Wei; Ma, Jun; Jiang, Jin; Huang, Zhuangsong; Cheng, Haijun; Pang, Suyan; Zhou, Yang; Zhai, Xuedong
Abstract: As a common animal feed additive, p-arsanilic acid (p-AsA) is thought to be excreted with little uptake and unchanged chemical structure, threatening the environment by potentially releasing more toxic inorganic arsenic. We herein investigated the removal of arsenic by in situ formed ferric (oxyhydr)oxides with the promotion of p-AsA degradation in Fe(II)/peroxydisulfate (PDS) system. Results showed that under acid conditions, p-AsA degraded very quickly and over 99% of p-AsA (5 μM) was degraded within 10 min at the optimal dosage of Fe(II) (100 μM) and PDS (150 μM) at pH 3, while less than 66.4% of arsenic was removed at pH 3–5. Higher pH (3–7) would inhibit the degradation of p-AsA but promote the arsenic removal. At pH 6–7, over 98.5% of total arsenic was removed, while the degradation efficiency of p-AsA was lower than 52.4%. HPLC-ICP-MS results indicated that the arsenic group was cleaved from p-AsA in the form of As(III) and then rapidly oxidized to As(V). FTIR and XPS analysis indicated that both As(V) products and residual p-AsA were bonded to ferric (oxyhydr)oxides via hydroxyl groups. Common cations (e.g., Na +, Ca 2+, Mg 2+ ) and anions such as Cl −, SO4 2−, CO3 2− had no significant influence on arsenic removal, while SiO3 2−, PO4 3− and HA inhibited the removal of total arsenic, mainly by affecting the zeta potential of iron particles. In summary, the Fe(II)/PDS process, as an efficient method for partial oxidation and simultaneous adsorption of p-AsA under near-neutral conditions, is expected to control the potential environmental risks of p-AsA. Graphical abstract: Image 1 Highlights: Fe(II)-activated PDS process was first studied for p-AsA removal. Arsenic removal with partial degradation of p-AsA at near-neutral pH was achieved. In situ formed ferric (oxyhydr)oxides could efficiently adsorb As(V) and p-AsA. Combined adsorption of As(V) and p-AsA was visually showed by HPLC-ICP-MS figures.